2011
DOI: 10.1136/heartjnl-2011-300867.78
|View full text |Cite
|
Sign up to set email alerts
|

The influence and function mechanism of hyperbaric oxygen pretreatment on myocardial ischemia reperfusion injury in rats

Abstract: Background and objective In recent years, coronary atherosclerotic heart disease become the major disease which is harmful to human health with a rising the trend of incidence. The world health organisation (WHO) predicts that by 2020 cardiovascular disease will become the primary cause of death in the world and Acute myocardial infarction as the most serious coronary heart disease type will become a culprit undoubtedly. Opening occlusion blood vessels early can effectively restore myocardial blood reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Ginsenoside Rg3 can also significantly reduce inflammatory factors (IL-6, TNF-α) produced by cardiomyocytes in rat models of myocardial ischemia-reperfusion. [19] Additionally, ginsenoside Rk3 can reduce the level of inflammatory cytokines in colon and inhibit the overproduction of TNF-α, IL-1β, and IL-6 by increasing the expression of zonula occludes proteins ZO-1, Occludin, and Claudin-1, thereby repairing intestinal barrier dysfunction and improving intestinal inflammation. [20]…”
Section: Regulation Of the Expression Level Of Inflammatory Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenoside Rg3 can also significantly reduce inflammatory factors (IL-6, TNF-α) produced by cardiomyocytes in rat models of myocardial ischemia-reperfusion. [19] Additionally, ginsenoside Rk3 can reduce the level of inflammatory cytokines in colon and inhibit the overproduction of TNF-α, IL-1β, and IL-6 by increasing the expression of zonula occludes proteins ZO-1, Occludin, and Claudin-1, thereby repairing intestinal barrier dysfunction and improving intestinal inflammation. [20]…”
Section: Regulation Of the Expression Level Of Inflammatory Factorsmentioning
confidence: 99%
“…found that ginsenoside Rh3 can inhibit the production and release of GM‐CSF in cells by reducing the phosphorylation levels of protein kinase C (PKC) and ERK, thereby reducing the production of inflammatory factors. Ginsenoside Rg3 can also significantly reduce inflammatory factors (IL‐6, TNF‐α) produced by cardiomyocytes in rat models of myocardial ischemia‐reperfusion [19] . Additionally, ginsenoside Rk3 can reduce the level of inflammatory cytokines in colon and inhibit the overproduction of TNF‐α, IL‐1β, and IL‐6 by increasing the expression of zonula occludes proteins ZO‐1, Occludin, and Claudin‐1, thereby repairing intestinal barrier dysfunction and improving intestinal inflammation [20] …”
Section: The Active Ingredient In Black Ginseng and Anti‐inflammatory...mentioning
confidence: 99%